G192 The Use of Faecal Calprotectin in Paediatric Inflammatory Bowel Disease. (4th June 2013) - O'Gorman, JR; Hussey, S; Russell, RK
Abstract : Aims: To evaluate the use of faecal calprotectin (FC) in children with suspected inflammatory bowel disease (IBD) in the previous year, and to establish if the number of negative endoscopies had been minimised without missing any cases of IBD. To assess the use of FC in established paediatric IBD. To analyse the cost benefit of the test. Methods: A retrospective analysis of FC measurements carried out between 1 st October 2011 and 30 th September 2012. FC measurements were obtained from the biochemistry department. Following a computerised search of the departmental records the presenting complaint, endoscopy result if applicable, diagnosis of IBD or alternative diagnosis, and follow-up or discharge were recorded for each patient. Patients were divided into those who were scoped based on their FC value and those who were not. Established IBD patients who had a FC test as part of their disease management were treated as a separate group. Results: 36 patients (55%) were not scoped. All 36 had at least one symptom indicative of IBD. 25 of these had a FC value of <50µg/g. 4 of these patients had a FC result > 200µg/g. None of these patients have been diagnosed with IBD. 17 patients were scoped (26%). 3 of these patients were diagnosed with IBD. Median FC for the group that were not scoped was 30µg/g (interquartile range (IQR) 30–760µg/g), compared with 126µg/g (IQR 52 –1, 590µg/g) in the group that were scoped. 8 patients with known IBD had a FC test when they became symptomatic and all FC values were consistent with GI inflammation. Overall, there was a 38% cost saving due to 44 unnecessary endoscopies being avoided. Conclusion: FC is a valuable test for excluding IBD in patients who present with abdominal pain and diarrhoea. FC can confirm relapse in symptomatic patients known to have IBD. When the test is used in these ways patients avoid an invasive procedure and the hospital is saved the cost of the endoscopy. However, guidelines are required to ensure the correct and appropriate use of this relatively new test.